Importance measure-based maintenance optimization strategy for pod slewing system - Chen, Liwei; Gao, Yansan; Dui, Hongyan; Xing, Liudong (Reliability engineering & system safety, 2021)
•The state of the art in the pod slewing system is discussed with its reliability.•The component importance is analyzed for the vulnerable components of the system.•The optimal maintenance strategy is investigated aiming to maximize the system performance.•Example solutions of pod slewing system are demonstrated for different mission time and cost. The pod slewing system is a complex hydraulic system that can realize the ship's yawing or reversing. Thus, its performance directly affects the maneuverability and flexibility of the ship. Existing research on the pod slewing system has mostly focused on its design and control aspects. This paper makes contributions by modeling the reliability of the pod slewing system and performing the component importance analysis using the integrated importance measure and the griffith importance measure to identify weak or vulnerable components of the system. Based on the importance analysis results, the optimal maintenance strategy is investigated, which maximizes the system performance subject to the constraint on the total maintenance costs. Example solutions to the optimized maintenance strategies are demonstrated for different mission time and different cost constraints.